2016
DOI: 10.1128/jcm.00012-16
|View full text |Cite
|
Sign up to set email alerts
|

A 5′ Nuclease Genotyping Assay for Identification of Macrolide-Resistant Mycoplasma genitalium in Clinical Specimens

Abstract: M ycoplasma genitalium is a sexually transmitted bacterium that causes nongonococcal urethritis in men and has been associated with cervicitis and pelvic inflammatory disease in women (1). The current recommended treatment of M. genitalium infection in Scandinavia is an extended course of oral macrolide. However, if empirical treatment of nongonococcal urethritis is initiated, usually only a single dose of azithromycin is given as treatment for suspected Chlamydia infection. Single-dose azithromycin treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…This is in line with our findings in a larger study [30] in our region and has also been reported by others from Norway [31], England [13], Australia [14], Denmark [32, 33], and the Netherlands [34]. Hence, macrolide resistance is an increasing problem [31, 3537].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with our findings in a larger study [30] in our region and has also been reported by others from Norway [31], England [13], Australia [14], Denmark [32, 33], and the Netherlands [34]. Hence, macrolide resistance is an increasing problem [31, 3537].…”
Section: Discussionsupporting
confidence: 93%
“…Wold et al presented a method using PCR with a TaqMan probe and polymorphism-specific forward primers ( 17 ), although only for specimens that had a cycle threshold ( C T ) of less than 32, thereby excluding samples with a lower organism load. PCR followed by pyrosequencing has also been presented ( 12 ), and recently, Kristiansen et al presented a 5′-nuclease genotyping assay for this purpose ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to most clinical guidelines, detection of M. genitalium should be followed by subsequent detection of macrolide resistancemediating mutations (MRMM) of the 23S rRNA gene (4). This is commonly achieved either via a second PCR and sequencing (6,7), via detection by various probe assays (8), or by melt curve analysis of amplicons (9). Diagnosing patients with macrolide-resistant M. genitalium via multiple PCR tests can be both time-and cost-inefficient.…”
mentioning
confidence: 99%